Credibility assessment of cold adaptive Pseudomonas jesenni MP1 and P. palleroniana N26 on growth, rhizosphere dynamics, nutrient status, and yield of the kidney bean cultivated in Indian Central Himalaya - Khan, Amir; Singh, Ajay Veer; Pareek, Navneet; Arya, Pratima; Upadhayay, Viabhav Kumar; Kumar Jugran, Arun; Kumar Mishra, Pankaj; Goel, Reeta (Frontiers in Plant Science, 2023)
Kidney bean (Phaseolus vulgaris) productivity and nutritional quality are declining due to less nutrient accessibility, poor soil health, and indigent agronomic practices in hilly regions, which collectively led to a fall in farmer’s income, and to malnutrition in consumers. Addressing such issues, the present investigation was designed to assess the impact of Pseudomonas jesenii MP1 and Pseudomonas palleroniana N26 treatment on soil health, microbial shift, yield, and nutrient status of the kidney bean in the Harsil and Chakrata locations of Indian Central Himalaya. P. jesenii MP1 and P. palleroniana N26 were characterized as cold adaptive PGPR as they possessed remarkable in vitro plant growth promoting traits. Further, field trial study with PGPR treatments demonstrated remarkable and prolific influence of both strains on yield, kidney bean nutrient status, and soil health at both geographical locations, which was indicated with improved grain yield (11.61%–23.78%), protein (6.13%–24.46%), and zinc content (21.86%–61.17%) over control. The metagenomic study revealed that use of bioinoculants also concentrated the nutrient mobilizing and plant beneficial microorganisms in the rhizosphere of the kidney bean. Moreover, correlation analysis also confirmed that the plant growth-promoting traits of P. jesenii MP1 and P. palleroniana N26 are the basis for improved yield and nutrient status of the kidney bean. Further, cluster and principal component analysis revealed that both P. jesenii MP1 and P. palleroniana N26 exhibited pronounced influence on yield attributes of the kidney bean at both the locations. At the Harsil location, the P. jesenii MP1-treated seed demonstrated highest grain yield over other treatments, whereas at Chakarata, P. jesenii MP1, and P. palleroniana N26 treatment showed almost equal enhancement (~23%) in grain yield over control. The above results revealed that these bioinoculants are efficient plant growth promoters and nutrient mobilizers; they could be used as green technology to improve human health and farmer’s income by enhancing soil health, yield, and nutrient status of the kidney bean at hilly regions.